2005
DOI: 10.1124/dmd.105.004374
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Chemotherapy and Drug Metabolism

Abstract: Chemotherapy involving the use of cytotoxic antineoplastic agents remains an important strategy in the overall management of patients with malignant tumors. As with most therapeutic agents, drug-metabolizing enzymes and drug transporters play key roles in determining the pharmacokinetics and overall disposition of antineoplastic agents in the body. In addition, metabolism and transport can be important contributors to 1) the toxicity produced by antineoplastic agents in normal host tissues and 2) the delicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…Our results showed a significant relationship with response to chemotherapy among individuals with GSTP1 Val/Val and ERCC2 A/A genotypes. Results of various subsequent studies have shown that consistent of nature of this relationship (Riddick et al, 2005). A similar association is found in of 2.19(1.15-6.21).…”
Section: Discussionsupporting
confidence: 73%
“…Our results showed a significant relationship with response to chemotherapy among individuals with GSTP1 Val/Val and ERCC2 A/A genotypes. Results of various subsequent studies have shown that consistent of nature of this relationship (Riddick et al, 2005). A similar association is found in of 2.19(1.15-6.21).…”
Section: Discussionsupporting
confidence: 73%
“…P450s expressed at higher levels in the tumour cells than in the surrounding normal tissue offer therapeutic options by the activation of prodrugs specifically in the cancer cells and avoiding undesirable systemic effects (see Riddick et al, 2005). In this respect, there are therapeutic options and opportunities arising from both the enhanced endogenous expression of CYP in tumours and CYP-mediated gene therapy.…”
Section: P450 As a Drug Target In Cancer Therapymentioning
confidence: 99%
“…The first evidence of their involvement in resistance to drugs used in chemotherapy have emerged from research published by scientific groups Schisswelbauer et al (1990), Tew (1994) and Hayes, Pulford, (1995). However, the relationship between GSTs and resistance to chemotherapy remains inconsistent (Riddick et al, 2005). This mechanism of resistance is related to the ability to regulate the action of enzymes involved in catalyzing electrophilic compounds harmful to cells from activation by cytochrome P-450 1A1 and 1B1 (Phase I).…”
Section: Mechanisms Of Resistance To Chemotherapeutic Agentsmentioning
confidence: 99%
“…We identified two types of resistance most relevant to BC: primary resistance, which corresponds to the clinical situation where the patient showed no response to therapy, and secondary or acquired resistance in which, initially, there is an observed response and a subsequent failure of the treatment regimen (Kroger et al, 1999). Several mechanisms may cause the phenotype of multidrug resistance to chemotherapy drugs and are well characterized in in vitro experiments, including alterations in systemic pharmacology (pharmacokinetics and metabolism), extracellular mechanisms (tumor environment, multicellular drug resistance), and cellular mechanisms (cellular www.intechopen.com pharmacology, activation and inactivation of drugs, modification of specific targets and regulatory pathways of apoptosis) (Leonessa et al, 2003, Riddick et al, 2005. Identification of factors that affect cell metabolism, which are related to drug resistance, will enable the identification of which patients are at particular risk of treatment failure.…”
Section: Mechanisms Of Resistance To Chemotherapeutic Agentsmentioning
confidence: 99%